Politici de incluziune socială - Arpinte, Daniel; Baboi, Adriana; Cace, Sorin; Tomescu, Cristina; Stănescu, Iulian (Calitatea Vieții, 2008)
This paper intends to be an analysis on social exclusion and social inclusion, from two perspectives: (1) based on the very concepts, as terms in social policies and (2) as distinct areas of public policy. In other words, we approach both the theoretical component, which defines and interprets the terms, particularly in the academic environment, and the institutional component of evolution and coverage at the level of social policies. The theoretical perspective starts from the fact that the terms of social exclusion and social inclusion come rather from the institutional environment, becoming later subject of the academic debates, too. First, we will present part of the theoretical considerations on the two concepts. Second, we will discuss the social inclusion as example of relation between the institutional knowledge reflected in a direction of public policy, and the scientific knowledge. In institutional terms, as area of public policy, we will describe the evolution of the social inclusion policies in the European Union and Romania. In the beginning, we will show the main moments of social policy construction at the European level and the position of the policies of social inclusion within them. Regarding Romania, we will show the reference points of the process of institutional construction regarding the social inclusion and we will identify its place and role within the public policies, during the pre-accession and post-accession to the European Union.